The Development of Human Resources Data Management Application at PT. Anugrah Laut Indonesia - Dahliar Ananda; Hetti Hidayati; Cahyana Cahyana (IJAIT (International Journal of Applied Information Technology), 2023)
Human Resources and employees are an important part of the continuity of a company. Employee data management is crucial for a company. Misconduct in managing it could lead to data inconsistency that may cause loss for the company. Previously, ALI Seafood use only office applications to make a simple record of the employee data raising some difficulties in managing the data. These difficulties such as human errors, low capability of the operator, loss of employee data, or errors in real-time data sharing. Centralized Information Technology (IT) system can assist a company in carrying out the process of managing employees, not only to overcome the difficulties above but also in carrying out the process of compiling information that is useful in making strategic decisions for company owners. This research carries out the process of analysis, design, and development of a web-based application and has been fully utilized at ALI Seafood. The main features of the application include managing the organization structure, employment data, attendance, payroll, and application management access. ALI Seafood HR application developed using Laravel framework and MySQL database.